Dynamix virtual event / Nur Dalilah Dahlan, Syaamil Adnan and Nur Hasmieza Zulkepli - Dahlan, Nur Dalilah; Adnan, Syaamil; Zulkepli, Nur Hasmieza (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
Dynamix Virtual Event is an event organized by Semester 3 Bachelor of Sports Management students, Faculty of Sports Science and Recreation, UiTM Seremban Campus. The Dynamix Virtual Event runs an esports event. Esports are video games which are played in professional competitions. This esports event aims to provide a sustainable platform for all levels of players to compete and show off their talents. This league was conducted fully online in accordance with the standard operating procedures (SOP) set under the National Recovery Plan - Phase 1. This event featured two well- known games amongst local esports fans namely Player Unknown's Battlegrounds (PUBG) and Mobile Legends: Bang Bang (MLBB). The event was held on 3rd and 4th July 2021 for PUBG Tournament and 10th and 11th July 2021 for MLBB Tournament. The tournament was open to all.